Preliminary Studies on the Intervarietal Crossability in Ber (Zizyphus Mauritiana Lam.) - Vashishtha, B B; Pareek, O P (Annals of Arid Zone, 2016)
Seb, Gola and Mundia are recommended varieties of her which are early maturing and good yielders but poor in transportable quality. Attempts were made to make reciprocal crosses of Seb, Gola, Sanaur-2, Katha and Umran. Results indicate that the maximum fruit set was rt"corded in Umran x Katha and minimum in Golax Sanaur-2. Mature fruits of SebxGola; SebxKatha, SebxUmran and UmranxSeb were harvested, rest had premature drop.